2015
DOI: 10.1371/journal.pone.0128252
|View full text |Cite
|
Sign up to set email alerts
|

Hypothesis of Long-Term Outcome after Coronary Revascularization in Japanese Patients Compared to Multiethnic Groups in the US

Abstract: BackgroundEthnicity has a significant impact on coronary artery disease (CAD). This study investigated the long-term outcomes of Japanese patients undergoing revascularization compared with US patients belonging to multiple ethnic groups.Methods and ResultsWe evaluated clinical outcomes, based on ethnicity, of patients included in the Coronary Revascularization Demonstrating Outcome (CREDO-Kyoto) and the Texas (US) Heart Institute Research Database (THIRDBase) registries. For the analysis, we included 8871 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
0
6
0
3
Order By: Relevance
“…The cardiac event rate was around 3% for cardiac death and 5% for MI [16]. On the other hand, others have reported that Japanese patients have a better prognosis after cardiovascular events compared with patients in North America [16,17]. The annual event rates of death and MI are about 2% in Japanese patients after coronary stent implantation in [18].…”
Section: Discussionmentioning
confidence: 99%
“…The cardiac event rate was around 3% for cardiac death and 5% for MI [16]. On the other hand, others have reported that Japanese patients have a better prognosis after cardiovascular events compared with patients in North America [16,17]. The annual event rates of death and MI are about 2% in Japanese patients after coronary stent implantation in [18].…”
Section: Discussionmentioning
confidence: 99%
“…10 Most studies might not have had a sufficiently long period to observe the development of CVD outcomes, especially mortality, as long-term care for a long lifespan is provided to Japanese people with CVD. [11][12][13] In addition, the confounding factors in the adjusted analyses differed among the reviewed studies.…”
Section: Discussionmentioning
confidence: 99%
“…10 The healthcare system of Japan (i.e., a freeaccess system to any medical institutions providing intensive therapy and close follow-up for CVD patients) may be a reason for such a low CVD mortality. [11][12][13] The characteristics of obesity and CVD in Japan are different from those in Western countries; thus, the relevance of MetS on CVD can be still discussed among Japanese people. [7][8][9][10]14 The summary of data specific to Japanese people can give an insight into the understanding of MetS on risk management of CVD.…”
Section: Introductionmentioning
confidence: 99%
“…Последний факт подтверждает и мультиэтни-ческое крупное регистровое исследование Кредо-Киото, которое включало 15580 пациентов, подверг-шихся КШ или ЧКВ. Так, самый низкий процент больных диабетом в данном регистре отмечен в евро-пеоидной (26,9%) и японской (39%) группах, а самый высокий процент -в африкано-американской (44%) и испанской (49,5%) этнических группах [50].…”
Section: таблицаunclassified